The Food-gut Human Axis: The Effects of Diet on Gut Microbiota and Metabolome - De Angelis, Maria; Garruti, Gabriella; Minervini, Fabio; Bonfrate, Leonilde; Portincasa, Piero; Gobbetti, Marco (Current Medicinal Chemistry, 2019)
Gut microbiota, the largest symbiont community hosted in human organism, is emerging as a pivotal player in the relationship between dietary habits and health. Oral and, especially, intestinal microbes metabolize dietary components, affecting human health by producing harmful or beneficial metabolites, which are involved in the incidence and progression of several intestinal related and non-related diseases. Habitual diet (Western, Agrarian and Mediterranean omnivore diets, vegetarian, vegan and gluten-free diets) drives the composition of the gut microbiota and metabolome. Within the dietary components, polymers (mainly fibers, proteins, fat and polyphenols) that are not hydrolyzed by human enzymes seem to be the main leads of the metabolic pathways of gut microbiota, which in turn directly influence the human metabolome. Specific relationships between diet and microbes, microbes and metabolites, microbes and immune functions and microbes and/or their metabolites and some human diseases are being established. Dietary treatments with fibers are the most effective to benefit the metabolome profile, by improving the synthesis of short chain fatty acids and decreasing the level of molecules, such as p-cresyl sulfate, indoxyl sulfate and trimethylamine N-oxide, involved in disease state. Based on the axis diet-microbiota-health, this review aims at describing the most recent knowledge oriented towards a profitable use of diet to provide benefits to human health, both directly and indirectly, through the activity of gut microbiota.
Keywords: Gut microbiota